光遺伝学的手法によるparvalbumin陽性細胞→錐体細胞シナプス伝達の長期増強 - 小林, 真之; 藤田, 智史; 小林, 理美 (日本薬理学会年会要旨集, 2023)
Repetitive nociception induces ectopic pain in the orofacial area by changing local neural circuits in the insular cortex (IC). Parvalbumin-immunopositive neurons (PVNs) send abundant projections to pyramidal neurons (PNs) and strongly suppress PN activities. Therefore, potentiation of PVNs→PNs inhibitory synaptic connections in the IC may suppress ectopic pain induction. In the present study, we investigated how repetitive stimuli by optogenetics applied to PVNs change the efficiency of synaptic connections from PVNs to PNs.First, we selectively expressed ChR2 in PVNs using Cre-loxP systems. Application of blue light to PVNs in the IC slice preparation induced action potentials in PVNs and inhibitory postsynaptic currents (IPSCs) in PNs. We investigated the protocol inducing long-term potentiation (LTP) of IPSCs. We found that optical stimuli similar to the theta burst stimulation increased to 142% of the amplitude of IPSCs. This LTP induction was independent from glutamate receptor activation. In the future, we apply this protocol to in vivo preparation to treat model animals with ectopic pain.